IL-6 signaling drives self-renewal and alternative activation of adipose tissue macrophages - Ackermann, Jan; Arndt, Lilli; Fröba, Janine; Lindhorst, Andreas; Glaß, Markus; Kirstein, Michaela; Hobusch, Constance; Wunderlich, F. Thomas; Braune, Julia; Gericke, Martin (Frontiers in Immunology, 2024)
Obesity is associated with chronic low-grade inflammation of adipose tissue (AT) and an increase of AT macrophages (ATMs) that is linked to the onset of type 2 diabetes.We have recently shown that neutralization of interleukin (IL)-6 in AT organ cultures inhibits proliferation of ATMs, which occurs preferentially in alternatively activated macrophage phenotype. In this study, we tested the effects of myeloid cell-specific IL-6Rα deficiency (Il6ra Δmyel ) on the murine metabolic phenotype, ATM polarization and proliferation after 20 weeks of HFD in vivo. Obese mice showed no differences in insulin sensitivity or histological markers of AT inflammation. Notably, we found a reduction of ATMs expressing the mannose receptor 1 (CD206), a putative marker for anti-inflammatory M2 macrophages, as well as a decrease of the proliferation marker Ki67 in ATMs lacking the IL-6Rα subunit. Importantly, organotypical AT culture and BMDM data of IL-4Rα knockout mice (Il4ra -/-) revealed that IL-6 mediates a shift towards the M2 phenotype independent from the IL-6/IL-4Rα axis, which sheds a new light on anti-inflammatory IL-6 signaling.